Wandering intrauterine contraceptive device: an unusual case of migration to the sigmoid colon. (2nd January 2021) - Samara, Elpida; Howe-Bush, Kerry; Portet, Mark; Howlett, David C
Abstract : An intrauterine device is a well-tolerated and widely used contraceptive method. A rare but major complication is perforation of the uterus and migration into the sigmoid colon. In this case report, a 33-year-old woman presented for follow up after placement of a copper-T intrauterine device 4 months previously. A clinical examination found significant tenderness on palpation, and the threads could not be detected. An ultrasound was conducted, which revealed no coil in the uterine cavity. The pelvic x-ray found it in the mid-pelvis and pelvic magnetic resonance imaging confirmed the position of the T-component at the mid-sigmoid colon. The patient underwent a sigmoidoscopy, which confirmed the position in the sigmoid colonic wall. The device was removed with an endoscopy without further complications. Uterine perforation and translocation to the sigmoid colon is an unusual complication of an intrauterine device. Removal of a translocated intrauterine device is recommended in all symptomatic cases.